Effect of hydrogen peroxide treatment on the concentration of volatile compound in coriander seeds oil - Rizka Wildani; Usman Ahmad; Mohamad Rafi; Slamet Ari Dwi Ratnanto (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2021)
Coriander seeds essential oil have shown some remarkable biological properties and health benefits. The coriander seeds used in Indonesia are imported and also treated with hydrogen peroxide before reaching consumers. Hydrogen peroxide is known to be a strong oxidizer, but so far, there has been no information that explains its effects on the essential oil composition and concentration in coriander seed. This study aims to determine the effect of using hydrogen peroxide and the drying method on the composition of essential oils in coriander seeds. Yield and volatile oil compounds were measured, and the results were compared between the hydrogen peroxide concentration (0,35 and 50% )  and drying method (mechanical drying (50 ℃) and room temperature drying). GC-MS analysis detected linalool as the most common volatile constituent in all treatments. The highest concentration of linalool compounds (70.16%) was found in seeds without hydrogen peroxide (0%) treatment combined with mechanical drying, followed by without hydrogen peroxide (0% H2O2) combined with room drying (23.74%), then by 35% hydrogen peroxide  combined with room drying (18.71%), 35% hydrogen peroxidecombined with mechanical drying (18.84%), 50% hydrogen peroxide  combined with room drying (22.18%) and by 50% hydrogen peroxide combined with mechanical drying (15.45%). Therefore, the yield was clearly affected only by hydrogen peroxide treatment where no hydrogen peroxide treatment gave the highest yield. The drying method did not have any significant effect on yield.